2019
DOI: 10.1016/j.lungcan.2019.04.016
|View full text |Cite
|
Sign up to set email alerts
|

Endobronchial and surgical treatment of pulmonary carcinoid tumors: A systematic literature review

Abstract: A B S T R A C TThe treatment of pulmonary carcinoid has changed over the last decades. Although surgical resection is still the gold standard, minimally invasive endobronchial procedures have emerged as a parenchyma sparing alternative for tumors located in the central airways. This review was performed to identify the optimal treatment strategy for pulmonary carcinoid, with a particular focus on the feasibility and outcome of parenchyma sparing techniques versus surgical resection. A systematic review of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
45
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 43 publications
(50 citation statements)
references
References 65 publications
0
45
0
Order By: Relevance
“…In two cases PET-CT was used for patient that had atypical carcinoids with neuroendocrine syndromes. Recent studies have demonstrated that the factors which lead to a negative outcome are lymph node metastasis, the histological differentiation degree, location of the tumor (central or peripheral) as well as tumor size (32).…”
Section: Discussionmentioning
confidence: 99%
“…In two cases PET-CT was used for patient that had atypical carcinoids with neuroendocrine syndromes. Recent studies have demonstrated that the factors which lead to a negative outcome are lymph node metastasis, the histological differentiation degree, location of the tumor (central or peripheral) as well as tumor size (32).…”
Section: Discussionmentioning
confidence: 99%
“…Typical carcinoids are less aggressive with 5-year survival rates of 87-100% and 10-year survival rates of 82-87%. Atypical carcinoids have a more malignant behaviour with significantly lower 5-and 10-year survival rates of 50-95% and 38-75%, respectively [9,10]. A recent review showed that tumour size, histology of atypical carcinoids, and lymph node metastasis have negative impacts on survival from pulmonary carcinoids [10].…”
Section: Epidemiology and Prognosismentioning
confidence: 99%
“…Atypical carcinoids have a more malignant behaviour with significantly lower 5-and 10-year survival rates of 50-95% and 38-75%, respectively [9,10]. A recent review showed that tumour size, histology of atypical carcinoids, and lymph node metastasis have negative impacts on survival from pulmonary carcinoids [10]. Regarding tumour diameter, YANG et al [11] showed that in patients with carcinoid tumour sizes ⩾3 cm, prognosis was significantly worse than for those with tumour sizes <3 cm.…”
Section: Epidemiology and Prognosismentioning
confidence: 99%
See 1 more Smart Citation
“…With this technique, several studies have shown excellent long-term outcome [6][7][8][9][10][11]. A recent systematic review by Reuling et al evaluated all studies utilizing either surgical resection and/or EBT [12]. The authors concluded that centrally located, small intraluminal pulmonary carcinoids, without signs of metastasis, can be treated with minimally invasive alternatives such as endobronchial treatment or parenchyma sparing surgical resection.…”
Section: Introductionmentioning
confidence: 99%